The Influence of Perceived Benefit, Perceived Risk, and Financial Literacy on Continuance Intention to Use E-Wallets in Financial Transactions - Khoirul Hikmah; Revika Novrita Putri; Diana Anggraini Kusumawati (AIBPM Publisher, 2025)
The purpose of this research is to determine the influence of perceived benefit, perceived risk, and financial literacy on continued intention to use e-wallets. The population in this study was all active undergraduate students of the UPN